ZnO-Zeolite nanocomposite application for photocatalytic degradation of procion red and its adsorption isotherm - Agustina, Tuty Emilia; Gayatri, Rianyza; Bahrin, David; Moeksin, Rosdiana; Gustini (Acta Polytechnica, 2022)
In this paper, the photocatalytic degradation of procion red dye, one of the most frequently used dyes in the textile industry, was studied. The objective of the research is to study the ZnO-Zeolite nanocomposite application to degrade procion red dye by using different irradiation sources. The adsorption isotherm was also investigated. The ZnO-Zeolite nanocomposite was prepared by a sol-gel process. Photodegradation test was applied under the sunlight irradiation, ultraviolet (UV) lamp, and in a darkroom. The dye degradation was also examined by the synthetic zeolite and ZnO for a comparison. Another objective of this study is to analyse the appropriate adsorption isotherm to describe the degradation process of procion red dye by using ZnO-Zeolite nanocomposite. The adsorption ability of the nanocomposite was described by Langmuir and Freundlich isotherms. The adsorption of the nanocomposite was reported to depend on the degradation time. The highest photodegradation result of 98.24 % was achieved by irradiating 50 mg/l of procion red dye under the sunlight for 120 minutes. The result showed that the Langmuir adsorption isotherm was the appropriate adsorption equation for the degradation process of procion red dye by using ZnO-Zeolite nanocomposite with R2 value of 0.995.